Multidisciplinary Scientific Cruises for Environmental Characterization in the Santos Basin – Methods and Sampling Design - Daniel L. Moreira; Adriana G. Dalto; Alberto G. Figueiredo Jr Figueiredo Jr; Aline M. Valerio; Amalia M. S. Detoni; Ana C. T. Bonecker; Camila N. Signori; Cláudia Namiki; Dalton K. Sasaki; Daniel V. Pupo; Danilo A. Silva; Deborah S. Kutner; et al. (Ocean and Coastal Research)
The Santos Basin (SB) is the main petroliferous basin in the Brazilian continental margin and one of the most studied marine areas in Brazil. However, historical data suggest that new efforts should be carried out to acquire quantitative biological data, especially in the deep sea, to establish the baseline of essential ocean variables in different ecosystems for future monitoring programs. The Brazilian energy company Petrobras planned and executed 24 oceanographic cruises over a period of 2 years to assess the benthic (SANSED cruise) and pelagic (SANAGU cruise) systems of the SB (356 days at sea in 2019 and 2021/2022). These efforts were part of the Santos Project, which comprised a comprehensive environmental study aimed at investigating benthic and pelagic variables to characterize ecology, biogeochemistry, thermohaline properties of water masses, and ocean circulation patterns, geomorphology, and sedimentology, as well as organic and inorganic chemistry. Here we present the detailed sampling designs and the field methods employed on board, during the SB scientific cruises. All sampling protocols were based on standardized approaches. For the benthos analyses, triplicate sediment samples were performed using a GOMEX-type box corer (0.25 m²) or a large modified Van Veen grab (0.75 m²) at 100 stations ranging from 25 to 2400 m depth. At each station, 25 geochemical and physico-chemical parameters were analyzed in addition to micro-, meio-, and macrofauna and living foraminifera samples. For the pelagic system, 60 stations were selected to investigate the plankton community, ranging in size from pico- to macroplankton, through vertical, horizontal, and oblique net hauls (20, 200, and 500 μm mesh size), as well as 25 biogeochemical parameters collected with an aid of a CTD-rosette sampler. Part of this scientific information also serves the Regional Environmental Characterization Project (PCR-BS) in support of Petrobras’ Santos Basin drilling licensing process led by the Brazilian Environmental Agency – IBAMA. This project contributes to the sustainable development of the SB, in line with the guidelines of the United Nations Decade of Ocean Science for Sustainable Development.